Abundance, Group Sizes and Habitat Use Patterns of Himalayan Tahr (Hemitragus jemlahicus) and Goral (Nemorhaedus goral) in Chenab Valley, Chamoli District (Uttarakhand) - Bhattacharya, T.; Sathyakumar, S. (Indian Forester, 2008)
The Chenab Valley in Urgam Reserve Forest of Chamoli District (Uttarakhand), was surveyed during March-April 2005, to estimate abundance and record observations on the group sizes, sex ratios, and habitat utilization patterns of Himalayan tahr and Goral. Encounter rate for tahr was 7.57 ± 1.17/hr scan and for goral, it was 0.47 ± 0.19 /km. Mean group size of Himalayan tahr (n=34), was 7.88±5.07 and for goral (n=21), it was 2.71±1.90. Himalayan tahr largely used the 2,500-3,500m altitude range, eastern and southern aspects, and steep slope categories. Goral mostly used the 2,000-2,500m altitude range, eastern and southern aspects, and moderate to steep slopes. Habitat utilization patterns of tahr and Goral show clear ecological separation between the two species. As Chenab Valley is located between the Kedarnath Wildlife Sanctuary and Nanda Devi Biosphere Reserve, it has significance and potential for conservation of Himalayan tahr, goral and other large mammals as this area lies outside the Protected Area network, but offers habitat contiguity and consequently movement of animal populations.